CATION COMPOSITION OF ORAL SECRETION IN PRIMARY SCHOOL-AGED CHILDREN - Vysochyna, I. L.; Kramarchuk, V. V. (Здобутки клінічної і експериментальної медицини, 2023)
Recurrent respiratory infections (RRIs) currently have the greatest medical and social burden among infectious diseases worldwide, with the highest prevalence and incidence rates of acute respiratory infections in children. Recent studies indicate the role of inadequate immune response and the development of recurrent acute respiratory infections (ARI) in children due to deficiencies in essential trace elements in the body, which are crucial for the proper functioning of physical barriers and the immune system. The hypothesis of our study assumed that, considering the recurrence of at least 6 episodes of ARI per year, children with RRIs may have changes in salivary ion levels, which could serve as a basis for local immune suppression of the upper respiratory mucosa. The aim – to investigate the levels of metals in the saliva of children of primary school age with recurrent respiratory infections in comparison with episodically ill peers and establish the relationship of these changes with the state of local immunity. Material and Methods. In the actual study, 40 children participated, with 30 of them (the main group) being children with recurrent respiratory infections and 10 other children who had episodic illnesses were assigned to the control group. The levels of metal cations in the saliva were examined using inductively coupled plasma atomic emission spectrometry, including essential metals such as copper, manganese, zinc, calcium, cobalt, potassium, magnesium, sodium, phosphorus, selenium, iron, chromium, and sulfur. Additionally, levels of conditionally essential metals like lithium, nickel, and boron were measured. The levels of secretory IgA and lysozyme in saliva were determined using the enzyme-linked immunosorbent assay method. Results. The main group was not homogeneous; therefore, we divided it into two clusters. Respondents in one cluster had significantly lower relative levels of essential ion content in saliva. Specifically, calcium was lower in 64 % (p=0.003), copper in 76.5 % (p=0.001), manganese in 41.1 % (p=0.008), magnesium in 64 % (p=0.02), and zinc in 58.8 % (p=0.027). This fact can be explained by their increased losses due to frequent inflammatory processes in the upper respiratory tract, resulting in higher daily replenishment needs compared to their peers. Correlation analysis revealed a connection between illness incidence and the levels of copper (p=0.008), sodium (p=0.00005), and phosphorus (p=0.028), indicating potential associations between saliva metal profiles and the frequency of ARI in children with RRIs. The presence of dental caries correlated with lithium (p=0.02), copper (p=0.032), and nickel levels (p=0.037). Integral indicators of local immunity, such as lysozyme and secretory IgA, exhibited correlations with metal levels in saliva (Li, Cu, Ni, Na, Co, P, Zn), confirming the hypothesis of their role in regulating immune reactions in the oral cavity. Conclusions. Cluster analysis of the metal profiles of the group of children with RRI shows its heterogeneity, 43 % of representatives of this cohort had significantly lower levels of calcium (p=0.003), copper (p=0.001), manganese (p=0.008), magnesium (p=0.02) and zinc (p=0.027) than the control group. Which may indicate the presence of deficient conditions in some children with PRI as a result of the increased need for their recovery. The presence of caries, the level of SIgA, lysozyme (clinical indicators of local immunity of the oral cavity) have certain relationships with the levels of essential and conditionally essential levels of salivary metals (Li, Cu, Ni, Na, Co, P, Zn), which indicates the benefit of the connection between the metal profile of saliva and the state of local immunity.